Quantitative melanoma diagnosis using spectral phasor analysis of hyperspectral imaging from label-free slices - Schuty, Bruno; Martínez, Sofía; Guerra, Analía; Lecumberry, Federico; Magliano, Julio; Malacrida, Leonel (Frontiers in Oncology, 2023)
Melanoma diagnosis traditionally relies on microscopic examination of hematoxylin and eosin (H&E) slides by dermatopathologists searching for specific architectural and cytological features. Unfortunately, no single molecular marker exists to reliably differentiate melanoma from benign lesions such as nevi. This study explores the potential of autofluorescent molecules within tissues to provide molecular fingerprints indicative of degenerated melanocytes in melanoma. Leveraging hyperspectral imaging (HSI) and spectral phasor analysis, we investigate autofluorescence patterns in melanoma compared to intradermal nevi. Using UV excitation and a commercial spectral confocal microscope, we acquired label-free HSI data from whole-slice samples. Our findings reveal distinct spectral phasor distributions between melanoma and intradermal nevi, with melanoma displaying a broader phasor phase distribution, signifying a more heterogeneous autofluorescence pattern. Notably, longer wavelengths associated with larger phases correlate with regions identified as melanoma by expert dermatopathologists using H&E staining. Quantitative analysis of phase and modulation histograms within the phasor clusters of five melanomas (with Breslow thicknesses ranging from 0.5 to 6 mm) and five intradermal nevi consistently highlights differences between the two groups. We further demonstrate the potential for discrimination of several melanocytic lesions using the center of mass comparisons of phase and modulation variables. Remarkably, modulation versus phase center of mass comparisons reveals strong statistical significance among the groups. Additionally, we identify the molecular endogenous markers responsible for tissue autofluorescence, which include Collagen, Elastin, NADH, FAD, and Melanin. In melanoma, autofluorescence is characterized by a higher phase contribution, indicating an increase in FAD and Melanin in the melanocyte nests. In contrast, NADH, Elastin, and Collagens dominate nevus autofluorescence. This work underscores the potential of autofluorescence and HSI-phasor analysis as valuable tools for quantifying tissue molecular fingerprints, thereby supporting more effective and quantitative melanoma diagnosis.